IL-33 and IL-10 Serum Levels Increase in MCI Patients Following Homotaurine Treatment - Toppi, Elisa; Sireno, Laura; Lembo, Micaela; Banaj, Nerisa; Messina, Beatrice; Golesorkhtafti, Sedigheh; Spalletta, Gianfranco; Bossù, Paola (Frontiers in Immunology, 2022)
Homotaurine is a potential therapeutic compound for treatment of Alzheimer’s disease (AD), but its efficacy is still under investigation. Emerging data have shown that other than neuroprotective, homotaurine is endowed with anti-inflammatory activities, though with still unclear underlying mechanisms. Inflammation plays a critical role in the pathogenesis of AD and we previously suggested that homotaurine supplementation in patients with amnestic mild cognitive impairment (MCI) plays beneficial effects associated to a decrease in the circulating levels of the pro-inflammatory cytokine IL-18. Here we report that MCI patients supplemented with homotaurine for 12 months show elevated serum levels of IL-10 and IL-33, as compared to baseline, in addition to the described IL-18 decrease. Furthermore, we observed a significant positive correlation between IL-10 and IL-33 levels after treatment but not at the baseline, underlining the effectiveness of the compound in modulating both cytokines in an inter-related fashion and in regulating the pro/anti-inflammation balance. Furthermore, the elevation of both IL-10 and IL-33 is significantly associated with an improvement of episodic memory of treated patients, as measured by the Delayed Verbal Ray Test. In conclusion, our results confirm that homotaurine treatment exerts an overall anti-inflammatory action in MCI patients, based not only on the down-regulation of pro-inflammatory IL-18, but also on up-regulation of the anti-inflammatory IL-33 and IL-10 cytokines, which in turn are associated with an amelioration of patient’s cognitive functions. Future studies should be addressed to investigate the molecular mechanisms of homotaurine anti-inflammatory activity and its therapeutic exploitation in early AD.